A Methodology for Evaluating Sustainable Building Technology to Raise the Efficiency of Urban Clusters: Analytical Study - Ahmed, Mai Niazy Moustafa; Goda, Abdullah Badawy Mohammed; Elattar, Sherif Mohamed Sabry (International Journal of Membrane Science and Technology, 2023)
Sustainability evaluation methodologies are distinguished from other evaluation tools, such as the LEED system and the BREEAM system, in that they include a new local evaluation methodology. The life cycle of a building is divided into distinct phases, including production of materials and components, construction and implementation, use/operation, maintenance, demolition, and disposal. Understanding the classification of assessment tools based on the building to be assessed, tool users, and building life cycle stages will inform selection of appropriate assessment tools and development of a comprehensive methodology. The study aimed to extract and evaluate opinions and perspectives from users, stakeholders, and researchers about the current status of sustainable technology in urban communities and to analyze the basic factors and indicators that contributed to the efficiency of urban communities and their relationship to sustainable technology. An inductive and analytical research was conducted using a questionnaire form on a sample of 100 participants to collect the opinions of users, relevant authorities, and researchers in the field. The questionnaire was designed to collect opinions and perspectives from different groups, including residents, local authorities (such as provincial officials, engineering administration, etc.), and experts in the field of sustainable technology. It covered a range of topics related to sustainable technology, including perceptions of current sustainability practices, barriers to implementation, potential areas for improvement, and proposals to enhance the efficiency of urban clusters. The research provided a comprehensive understanding of views on sustainable technology and help identify key areas for evaluation and improvement.